Kontribusi Pemikiran KH. Ahmad Dahlan dan KH. Hasyim Asy'ari terhadap Modernisasi Pendidikan Islam di Indonesia - Wahyono; Sholikatus Sofiah; Ana Lutfiana; Mulyanto Abdullah Khoir (TSAQOFAH, 2026)
The modernization of Islamic education in Indonesia faces challenges in integrating Islamic values, scientific developments, and the social needs of modern society without losing its religious identity. In this context, the ideas of Islamic reformers play a strategic role in building an educational paradigm that is adaptive to changing times. This study aimed to analyze the contributions of KH. Ahmad Dahlan’s and KH. Hasyim Asy’ari’s thought to the modernization of Islamic education in Indonesia, particularly in terms of educational goals, knowledge integration, institutional systems, learning methods, and students’ character development. The study employed a qualitative method with a library research approach through a critical analysis of the works of both figures, academic literature, and relevant historical sources. The results showed that KH. Ahmad Dahlan contributed through the integration of religious and general knowledge, the development of a modern education system, and an educational orientation toward community empowerment through Muhammadiyah educational institutions. Meanwhile, KH. Hasyim Asy’ari contributed through strengthening the scholarly tradition of Islamic boarding schools, instilling the values of adab and morality, and developing students’ character based on Islamic values. The ideas of both figures demonstrate an integration between educational system reform and the preservation of Islamic traditions, which serves as an important foundation for the development of Islamic education in Indonesia. This study concludes that the ideas of KH. Ahmad Dahlan and KH. Hasyim Asy’ari remain relevant to building an Islamic education model that is responsive to global dynamics, oriented toward the development of knowledge, and rooted in Islamic spiritual and moral values. These findings enrich the literature on Islamic educational thought and emphasize the importance of reconstructing contemporary Islamic education by integrating modern ideas with Islamic scholarly traditions in addressing the educational challenges of the twenty-first century.